2022
DOI: 10.15562/bmj.v11i3.3666
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Sentul fruit peel extract (Sandoricum koetjape) against Streptococcus mutans and Staphylococcus aureus

Abstract: Introduction: Infectious mouth diseases are caused by microorganisms such as      Staphylococcus aureus and Streptococcus mutans. Sentul fruit peel extract contains several phytochemical compounds, flavonoid compounds, saponins and tannins are aromatic hydroxyl groups that act as antibacterial so that they can be used as a treatment for infections of the mouth. This study aimed to determine the inhibitory ability of Sentul fruit peel extract (Sandoricum koetjape) against Streptococcus mutans and Staphylococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, few studies have reported the nanotherapeutic effects of koetjapic acid in some other diseases [ 35 ]. Koetjapic acid nanoparticles were synthesised and demonstrated antibacterial potential against streptococcus species [ 75 ]. A recent study demonstrated that nanoparticles containing koetjapic acid extracts were synthesised and tested on the gingivitis rat models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have reported the nanotherapeutic effects of koetjapic acid in some other diseases [ 35 ]. Koetjapic acid nanoparticles were synthesised and demonstrated antibacterial potential against streptococcus species [ 75 ]. A recent study demonstrated that nanoparticles containing koetjapic acid extracts were synthesised and tested on the gingivitis rat models.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that nanoparticles containing koetjapic acid extracts were synthesised and tested on the gingivitis rat models. It was revealed that the nanoformulation of koetjapic acid at a concentration of 2.4% decreased the number of streptococcus colonies after administration [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…positive response (I. Wirata 2002) There was even a suggestion that the sinetron should be re-broadcast or a play performed live at the Bali Arts Festival, because this would be an excellent way to remember Rasta Sindhu as one of Bali's most talented modern writers. One reason that the story has been able to maintain public attention so strongly, many years after its initial publication, is that caste confl ict remains a major point of contention in Balinese public discourse, even in the twenty-fi rst century.…”
Section: Intergenerational Caste Confl Ictmentioning
confidence: 99%